Peran Badan Penanggulangan Bencana Daerah Kota Padang dalam Kesiapsiagaan Menghadapi Bencana Cuaca Ekstrem di Kota Padang - Ari Rinaldo; Zikri Alhadi (YASIN, 2026)
Extreme weather disasters are among the hydrometeorological threats that frequently occur in Padang City and have the potential to cause fatalities, infrastructure damage, and disruptions to the community’s social and economic activities. This condition requires the Padang City Regional Disaster Management Agency (BPBD) to optimize its role in improving community preparedness as part of disaster risk reduction efforts. This study aimed to analyze the role of BPBD Padang City in preparedness for extreme weather disasters and identify the supporting and inhibiting factors in its implementation. The study employed a qualitative method with a descriptive approach. Data were obtained through observation, in-depth interviews, and documentation and were subsequently analyzed using the interactive model of Miles, Huberman, and Saldaña, which comprises data condensation, data display, and conclusion drawing. Data validity was examined through source triangulation and method triangulation. The results showed that BPBD Padang City had performed its roles as a stabilizer, innovator, modernizer, pioneer, and direct implementer in improving preparedness for extreme weather disasters. These roles were manifested through the operation of an early warning system, the utilization of information technology, cross-sectoral coordination, the implementation of disaster awareness programs and simulations, and direct emergency response in the field. Factors supporting the implementation of BPBD’s roles included the presence of the Disaster Management Operations Control Center, the utilization of information technology, interagency coordination, and community education programs. Meanwhile, the inhibiting factors included low public awareness, limited human resources and facilities and infrastructure, and the suboptimal integration of interagency information systems. This study concluded that effective preparedness for extreme weather disasters requires strengthened institutional capacity, improved community disaster literacy, and optimized cross-sectoral coordination. These findings provide practical implications for BPBD and relevant stakeholders in formulating disaster preparedness strategies that are more integrated and responsive to extreme weather risks in Padang City.